PEMBERDAYAAN UMKM MELALUI LITERASI DIGITAL DAN PELATIHAN PEMASARAN ONLINE DI KELURAHAN KALISARI KOTA SURABAYA - Firda Cahaya Fironika; Adisty Della Firnanda; Rangga Rasendriya Putra Arianto; Binti Azizatun Nafi’ah (ABIDUMASY, 2026)
This community service program aimed to empower MSMEs in Kalisari Urban Village, Surabaya, through digitalliteracy enhancement and online marketing training. The program was initiated due to the limited digitalknowledge and marketing skills among MSME actors in promoting their products online. A participatory andeducational approach was employed, consisting of needs assessment, socialization, technical training, and directmentoring. The training focused on utilizing WhatsApp Business, social media (Instagram, Facebook, TikTok),and marketplaces such as Shopee and Tokopedia. The results showed significant improvements in participants’understanding, technical skills, and independence in applying digital marketing strategies. MSME actors wereable to create promotional content, manage business accounts, and utilize platform features to expand their marketreach. The training also fostered an innovative and self-reliant mindset, helping build a sustainable communitybasedbusiness ecosystem in the digital era.Keywords: MSMEs, digital literacy, online marketing, digital training, community empowerment